University Students’ Impulse Buying On Tiktok Shop: The Predictive Roles Of Financial Literacy And Promotional Exposure - Queena Naurah Arum Azalia; Riyanti Agustin; Aninda Widyana; Tantri Paraswati; Muhammad Raihan Zuhruful Ulum (Universitas Indonesia Membangun (Inaba), 2026)
Social commerce increasingly places university students in shopping situations where entertainment, creator content, peer cues, promotional incentives, and immediate transaction facilities are integrated into a continuous experience. This study examines the predictive roles of financial literacy and promotional exposure in university students’ impulse buying on TikTok Shop. A quantitative cross-sectional survey was conducted among undergraduate students at the Faculty of Economics and Business Education, Universitas Pendidikan Indonesia, who had purchased products through TikTok Shop. Of 126 submitted responses, 100 usable responses met the eligibility and completeness criteria and were analyzed using Partial Least Squares Structural Equation Modeling with SmartPLS 4. The results indicate that financial literacy was negatively associated with impulse buying and showed a significant predictive relationship (β = -0.263, t = 2.154, p = .031). In contrast, promotional exposure was positively associated with impulse buying and demonstrated a stronger positive predictive relationship (β = 0.431, t = 4.416, p < .001). Together, the two predictors explained 27.2% of the variance in impulse buying. Financial literacy showed a small-to-moderate effect size, while promotional exposure showed a moderate effect size. These findings suggest that students’ impulse buying reflects the tension between internal financial self-regulation and persuasive promotional stimuli in short-video social commerce. The study highlights the importance of ethical promotional practices and practical financial literacy education that addresses students’ actual digital consumption behavior.